Factores determinantes de la esperanza de vida en Chile - Barahona-Urbina, Planck (2011)
Introduction: In recent decades Chile has experienced strong economic growth that has improved citizens living conditions. Objectives: To determine factors associated with life expectancy in Chile. Design: Econometric analysis. Setting: Chile. Interventions: Application of multiple regression models for the analysis of life expectancy in Chile. Aggregated data of the National Institute of Statistics (INE) and the Central Bank of Chile for the period 1988-2008 was used. Dependent variable was life expectancy in years and explanatory variables GDP per capita, number of physicians, number of nurses and public health spending. Main outcome measures: Factors associated with life expectancy. Results: Results show that per capita income, number of physicians, number of nurses and health spending were statistically significant, i.e., had positive effect on people’s life expectancy. Conclusions: Results have shown how beneficial quantitatively increased GDP per capita may be for longer life expectancy. Likewise, results suggest the positive effect of an increase in medical personnel in the country since this variable has satisfied the ever-increasing health demand of the population. Variable health budget increase had positive effect on improving living conditions in Chile.